2019
DOI: 10.1002/da.22980
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dignity therapy for patients with advanced cancer: A systematic review and meta‐analysis of 10 randomized controlled trials

Abstract: Background Dignity is a vitally important aspect of the lives of advanced cancer patients. We conducted a systematic review and meta‐analysis of the effectiveness of dignity therapy in this patient population. Methods We searched for randomized controlled trials comparing dignity therapy versus standard care for patients with advanced cancer in five comprehensive databases (March 2019), two clinical trial registries and one gray literature database (August 2019). The quality of the studies was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…Reviews of the many studies carried out in the last years in at least eleven countries confirm that DT is feasible and overall accepted in various clinical and cultural realities, and it is effective in promoting patient/family sense of dignity, meaning, and quality of life, while reducing psychological and dignity related distress [59][60][61][62][63]. A recent meta-analysis examining ten RCT and confronting DT applied in cancer palliative care to standard care demonstrated that DT significantly decreased anxiety, depression, and dignity related distress in advanced cancer patients [64]. A different meta-analysis opposing DT to control conditions further evidenced that DT promoted dignity, existential, and social support domains [60].…”
Section: The Structure Of Dignity Therapymentioning
confidence: 99%
“…Reviews of the many studies carried out in the last years in at least eleven countries confirm that DT is feasible and overall accepted in various clinical and cultural realities, and it is effective in promoting patient/family sense of dignity, meaning, and quality of life, while reducing psychological and dignity related distress [59][60][61][62][63]. A recent meta-analysis examining ten RCT and confronting DT applied in cancer palliative care to standard care demonstrated that DT significantly decreased anxiety, depression, and dignity related distress in advanced cancer patients [64]. A different meta-analysis opposing DT to control conditions further evidenced that DT promoted dignity, existential, and social support domains [60].…”
Section: The Structure Of Dignity Therapymentioning
confidence: 99%
“…Moreover, patients with different advanced non-malignant disease had similar ratings of moderate to extreme loss of dignity (Chochinov et al, 2016). Research on the efficacy of DT for dignity-related distress produced mixed results (Donato et al, 2016;Li et al, 2020). For example, previous studies found no significant differences between DT and palliative care on dignity (e.g., Chochinov et al, 2011;Hall et al, 2011;Vuksanovic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas terminally ill patients report benefits from DT for themselves and their families, the effects on psychological outcomes are less clear ( Fitchett et al, 2015 ; Donato et al, 2016 ). For instance, a meta-analysis showed that DT did not reduce depression and anxiety of patients compared with the standard care ( Xiao et al, 2019 ), whereas other reviews revealed a significant improvement of these psychological symptoms ( Li et al, 2020 ) or mixed results ( Sposato, 2016 ). The discrepancy between reported benefits and inconclusive evidence of DT may be due to several issues, such as low levels of distress at baseline ( Martínez et al, 2017 ), the possibility of delayed effects ( Fitchett et al, 2015 ), measures not sensitive enough to detect a psychological change ( Sposato, 2016 ; Xiao et al, 2019 ) and lack of high quality study designs ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors are similarly aware of increasing interest in non-structured therapies (such as dignity therapy ( Li et al, 2019 )) for managing depressive and anxious symptomatology in those with advanced cancer. However, there are barriers in transforming many of the meaning-centred therapies into an online intervention.…”
Section: Discussionmentioning
confidence: 99%